Preliminary findings on the possible role of B-lymphocyte stimulator (BLyS) on diabetes-related periodontitis - Marx Haddley Ferreira DRUMOND; Luciano Eduardo PUHL; Poliana Mendes DUARTE; Tamires Szeremeske de MIRANDA; Juliana Trindade CLEMENTE-NAPIMOGA; Daiane Cristina PERUZZO; Elizabeth Ferreira MARTINEZ; Marcelo Henrique NAPIMOGA (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract The possible role of B-cell growth and differentiation-related cytokines on the pathogenesis of diabetes-related periodontitis has not been addressed so far. The aim of this study was to evaluate the effects of diabetes mellitus (DM) on the gene expression of proliferation-inducing ligand (APRIL) and B-lymphocyte stimulator (BLyS), two major cytokines associated to survival, differentiation and maturation of B cells in biopsies from gingival tissue with periodontitis. Gingival biopsies were obtained from subjects with periodontitis (n = 17), with periodontitis and DM (n = 19) as well as from periodontally and systemically healthy controls (n = 10). Gene expressions for APRIL, BLyS, RANKL, OPG, TRAP and DC-STAMP were evaluated using qPCR. The expressions APRIL, BLyS, RANKL, OPG, TRAP and DC-STAMP were all higher in both periodontitis groups when compared to the control group (p < 0.05). Furthermore, the expressions of BLyS, TRAP and RANKL were significantly higher in the subjects with periodontitis and DM when compared to those with periodontitis alone (p < 0.05). The mRNA levels of BLyS correlated positively with RANKL in the subjects with periodontitis and DM (p < 0.05). BLyS is overexpressed in periodontitis tissues of subjects with type 2 DM, suggesting a possible role of this cytokine on the pathogenesis DM-related periodontitis.